Short Communication Development of Ultraviolet Spectrophotometric Methods for Analysis of Stavudine in Bulk and Pharmaceutical Dosage Forms: stavudine, spectrophotometry, phosphate buffer, correlation coefficient (Biological Sciences - PJSIR, 2010)
A UV spectrophotometric method was developed and validated for the quantitative determination of stavudine, one of the first line regimens in antiretroviral therapy. The different analytical routine parameters such as linearity, precision, accuracy, limit of detection and limit of quantification were determined according to International Conference  on Harmonization guidelines. Effect of various temperatures (25,50 and 60 °C) on stavudine solution in phosphate buffer pH 6.8 was also studied. Absorbance maximum in phosphate buffer pH 6.8 was found to be 266 nm. Beer’s law is obeyed over concentration range of 3-24 mg/mL with correlation coefficient (r2) value 0.999. The results were validated statistically and by recovery study. Degradation of stavudine was more at high temperature. The proposed method is highly sensitive, precise, cheap, reliable and less time consuming for estimation of stavudine in bulk as well as in pharmaceutical dosage forms.